2007
DOI: 10.1577/m06-049.1
|View full text |Cite
|
Sign up to set email alerts
|

Spawning Characteristics of Adfluvial Rainbow Trout in a North Idaho Stream: Implications for Error in Redd Counts

Abstract: We examined redd microhabitat characteristics of an adfluvial population of rainbow trout Oncorhynchus mykiss in Trail Creek, a third-order tributary to Deep Creek in the Kootenai River drainage, Idaho. We also monitored timing of spawning in relation to stream temperature and discharge. A total of 103 suspected redds were found; 51 of these were measured and checked for the presence of eggs. Thirty-four were actual redds (contained eggs), while 17 were test digs that did not contain eggs. Rainbow trout began … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
5
9
0
Order By: Relevance
“…The characteristics of microhabitat variables associated with the redds observed in this study were similar to other published values for adfluvial rainbow trout (Holecek & Walters 2007) and resident redband trout (Muhlfeld 2002). The characteristics of microhabitat variables associated with the redds observed in this study were similar to other published values for adfluvial rainbow trout (Holecek & Walters 2007) and resident redband trout (Muhlfeld 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The characteristics of microhabitat variables associated with the redds observed in this study were similar to other published values for adfluvial rainbow trout (Holecek & Walters 2007) and resident redband trout (Muhlfeld 2002). The characteristics of microhabitat variables associated with the redds observed in this study were similar to other published values for adfluvial rainbow trout (Holecek & Walters 2007) and resident redband trout (Muhlfeld 2002).…”
Section: Discussionsupporting
confidence: 89%
“…The overlap in the spawning timing between the two species can be partly attributed to the reproductive timing of the original rainbow trout strains that spawn in the same season even in other regions. Such a relationship between the initiation of spawning and water fluctuation has also been reported in other spring-spawning populations of Sakhalin taimen (Fukushima 1994) as well as in golden trout O. mykiss aguabonita (Knapp & Vredenberg 1996), redband trout O. mykiss gairdneri (Muhlfeld 2002) and in adfluvial rainbow trout (Holecek & Walters 2007). In this study area, most streams are frozen until mid-March and freshets may suddenly occur in late March or early April due to the melting of snow and ice.…”
Section: Discussionsupporting
confidence: 84%
“…As a result, counting redds is easier and less expensive than more intrusive enumeration methods such as tagging, trapping, and underwater observation. Although there can be substantial error in redd counts (Bonneau and LaBar 1997;Dunham et al 2001;Holecek and Walters 2007), research has shown that this metric is strongly correlated with estimates of adult escapement (Rieman and Myers 1997;Maxell 1999;Dunham et al 2001), especially when experienced surveyors are used (Muhlfeld et al 2006).…”
mentioning
confidence: 99%
“…America also exhibit a variety of spawning movement patterns including adfluvial (i.e., lake rearing and stream spawning; Cope 1956;Downs et al 2006;Holecek and Walters 2007;Barnett and Paige 2013), fluvial (i.e., larger spawning and rearing movements within streams; Colyer et al 2005;AlChokhachy and Budy 2008;Pierce et al 2009), and tributary residency (Young 1995), and multiple movement patterns are often demonstrated within a single watershed (Al-Chokhachy and Budy 2008). The diversity of potamodromous trout spawning movements is thought to be part of a complex set of life history characteristics that have evolved in response to frequent changes in the spatial and temporal availability of suitable habitat (Gresswell et al 1994;Northcote 1997;Dunham et al 2003).…”
Section: ) Potamodromous Trout Populations Of Western Northmentioning
confidence: 99%
“…Redd surveys are a common method for assessing spawning activity in salmonids because they are relatively inexpensive and nondisruptive (Dunham et al 2001;Holecek and Walters 2007). Monitoring salmonid redds can provide some of the life history data required to determine the conservation status of the fish.…”
Section: ) Potamodromous Trout Populations Of Western Northmentioning
confidence: 99%